Enhancing Quality Assurance in Teacher Education: Development of a PPEPP-Based Micro Teaching Assessment System - Keith Francis Ratumbuisang; Herry Sumual; Orbanus Naharia; Mario Tulenan Parinsi; Hendry Tamboto; Ruth Umbase; Donal Ratu; Rolles N. Palilingan (International Journal of Information Technology and Education, 2025)
Micro teaching assessment plays a strategic role in preparing prospective teachers to develop professional teaching competencies. However, in many teacher education institutions, the assessment process is still conducted manually, inconsistently, and without adequate integration into institutional quality assurance systems. These limitations reduce the effectiveness of assessment as a tool for educational management and continuous improvement. This study aims to develop and evaluate a Micro Teaching Assessment Information System based on the PPEPP cycle (Planning, Implementation, Evaluation, Control, and Improvement) to support more systematic, transparent, and accountable assessment management. The research employed a Research and Development (R&D) approach consisting of needs analysis, system design, prototype development, expert validation, field testing, and product revision. Data were collected through observations, interviews, questionnaires, and system usability testing, and were analyzed using descriptive and inferential statistics as well as thematic analysis. The results indicate that the developed system achieved high levels of feasibility and usability, improved assessment efficiency, standardized evaluation procedures, enhanced the quality of feedback, and enabled real-time monitoring of student performance. The study concludes that the PPEPP-based assessment information system provides an effective technological solution for strengthening micro teaching management, supporting data-driven decision-making, and promoting sustainable quality improvement in teacher education.